Recycling cupola slag for manufacturing magnesium metal matrix composites with alumina for electric vehicle battery pack system housings - Andrea Sánchez-Arroyo; Mario Rodríguez-Reyes; Gerardo Daniel Olvera-Romero; José Refugio Parga-Torres; Zully Matamoros-Veloza; Brandon Osvaldo Villarreal-Fuentes; Dagoberto Vázquez-Obregón (Next Sustainability)
This study investigated magnesium matrix composites reinforced with cupola slag (a source of CaSiO₃) and Al₂O₃ particles for potential application in battery pack system (BPS) housings. The composites were fabricated via powder metallurgy, resulting in four systems: a pure magnesium system (100 M), a composite with 85 wt% Mg and 15 wt% cupola slag (85M-15C), and two hybrid composites with 85 wt% Mg combined with 12.5 wt% and 5 wt% cupola slag, and 2.5 wt% and 5 wt% Al₂O₃, respectively, forming the 85M-12.5C-2.5 A and 85M-10C-5A systems. Their mechanical properties and corrosion resistance in a 3.5 wt% NaCl solution were systematically evaluated. Microstructural analysis revealed a significant grain size reduction in the reinforced systems, with the 85M-12.5C-2.5 A system achieving an average grain size of 9.4 µm compared to 22.5 µm in the unreinforced 100 M system. The incorporation of CaSiO₃ and Al₂O₃ reinforcements improved microhardness by up to 55 % and increased compressive strength to a maximum of 329.13 MPa. These enhancements were attributed to grain size and the synergistic effects of micro- and nano-reinforcements. Additionally, the reinforced composites demonstrated superior corrosion resistance, as evidenced by reduced degradation rates in the NaCl solution. This improvement was attributed to the formation of protective Mg(OH)₂ layers, with the 85M-10C-5A system exhibiting the lowest corrosion current density (122 μA/cm²). These findings underscore the potential of magnesium matrix composites reinforced with cupola slag and Al₂O₃ as lightweight, durable, and sustainable materials for BPS housings, addressing both performance and environmental considerations.